Desenvolvimento formal de aplicações para smartcards - Gomes, Bruno Emerson Gurgel (2012)
Smart card applications represent a growing market. Usually this kind of application manipulate and store critical information that requires some level of security, such as financial or confidential information. The quality and trustworthiness of smart card software can be improved through a rigorous development process that embraces formal techniques of software engineering. In this work we propose the BSmart method, a specialization of the B formal method dedicated to the development of smart card Java Card applications. The method describes how a Java Card application can be generated from a B refinement process of its formal abstract specification. The development is supported by a set of tools, which automates the generation of some required refinements and the translation to Java Card client (host) and server (applet) applications. With respect to verification, the method development process was formalized and verified in the B method, using the Atelier B tool [Cle12a]. We emphasize that the Java Card application is translated from the last stage of refinement, named implementation. This translation process was specified in ASF+SDF [BKV08], describing the grammar of both languages (SDF) and the code transformations through rewrite rules (ASF). This specification was an important support during the translator development and contributes to the tool documentation. We also emphasize the KitSmart library [Dut06, San12], an essential component of BSmart, containing models of all 93 classes/interfaces of Java Card API 2:2:2, of Java/Java Card data types and machines that can be useful for the specifier, but are not part of the standard Java Card library. In other to validate the method, its tool support and the KitSmart, we developed an electronic passport application following the BSmart method. We believe that the results reached in this work contribute to Java Card development, allowing the generation of complete (client and server components), and less subject to errors, Java Card applications.